ANTI-TUMOR EFFECT OF CACTUS POLYSACCHARIDES ON LUNG SQUAMOUS CARCINOMA CELLS (SK-MES-1) - Li, Weiling; Wu, Di; Wei, Bin; Wang, Shuang; Sun, Haixia; Li, Xinli; Zhang, Fei; Zhang, Cuili; Xin, YI (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Cactus polysaccharides are the active components of Opuntia dillenii which have been used extensively in folk medicine. In this study, we investigate the anti-tumor effect of cactus polysaccharides on lung squamous carcinoma cells SK-MES-1. Materials and Methods: The inhibitory effect of Cactus polysaccharides on lung squamous carcinoma cells were detected by MTT assay. Cell cycle was determined by flow cytometry and cell apoptosis was determined by AnnexinV assay. Western-blotting was applied to detect P53 and PTEN protein expression in the cells treated with cactus polysaccharides. Results: Results showed that different concentrations of wild cactus polysaccharides prevent SK-MES-1 cells growth and induces S phase arrest. The data also revealed that cactus polysaccharides cause apoptosis in SK-MES-1 cells determined by Annexin-V assay. Furthermore, cactus polysaccharides induced growth arrest and apoptosis may be due to the increase of P53 and phosphatase and tension homolog deleted on chromosome ten (PTEN) protein. Conclusion: Cactus polysaccharides have anti-tumor activity on lung squamous carcinoma cells.